2012
DOI: 10.2527/jas.2012-5330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed restriction on hormones, performance, carcass traits, and meat quality in immunocastrated pigs1

Abstract: The aim of this study was to assess the effect of feed restriction applied to immunocastrated pigs in the period after the second vaccination (V2) against GnRH on hormonal status, performance, carcass traits, and meat quality. Immunocastrated pigs (IC) were compared with entire males (EM) and surgical castrates fed ad libitum. Pigs (Large White × Landrace) × Pietrain were either left entire or surgically castrated within 1 wk after birth (SC, n = 22). At 83 d of age, the entire males were further allotted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 46 publications
12
62
3
Order By: Relevance
“…Both trials confirm the better G : F ratio in ad libitum fed EM and IM in comparison with SCM (Dunshea et al, 2001;Morales et al, 2010;Batorek et al, 2012b). This is a result of lower feed intake without clear differences in ADG.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Both trials confirm the better G : F ratio in ad libitum fed EM and IM in comparison with SCM (Dunshea et al, 2001;Morales et al, 2010;Batorek et al, 2012b). This is a result of lower feed intake without clear differences in ADG.…”
Section: Discussionsupporting
confidence: 64%
“…This is a result of lower feed intake without clear differences in ADG. After the second vaccination, however, ADFI and DG of IM strongly increases (Schmidt et al, 2011;Batorek et al, 2012b;Weiler et al, 2013). We showed that this increase is very abrupt and noticeable within 1 week after the second injection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, in this study, the cortisol levels in the blood were not altered by either immunocastration or the addition of RAC, suggesting that these treatments did not induce stress in the animals. These findings agree with Batorek et al (2012).…”
Section: Stress Parameterssupporting
confidence: 82%
“…The samples of subcutaneous fat were taken at the level of the last rib for determination of androstenone and skatole concentrations. They were measured using an HPLC according to the procedures described by Batorek et al (2012). Concentrations were expressed per gram of the lipid fraction from the adipose tissue.…”
Section: Animalsmentioning
confidence: 99%